Active Teaching and Learning: Educational Trends and Practices - Carlos Pérez-González; Delfín Ortega-Sánchez (Education Sciences, 2025)
Educational research published over the past five years reveals a sustained shift from content-delivery models toward learning ecologies that explicitly interweave place, subjectivity, and institutional responsibility [...]